1994
DOI: 10.3801/iafss.fss.4-1101
|View full text |Cite
|
Sign up to set email alerts
|

A Concrete Model Considering The Load History Applied To Centrally Loaded Columns Under Fire Attack

Abstract: ABSTRACT.The description is given of a model for concrete in compression at elevated temperature that incorporates elastic, plastic and creep strains as functions of the temperature and stress history. The plastic strain and the creep strain depend on the stress history and the stiffness of the model depends on the load level during fire exposure. The proposed model is an updated version of a model presented earlier by one of the author [I].Fifteen fire resistance tests have been performed on reinforced concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…This generic behaviour was initially proposed by Schneider [17] and has been approved by a draft committee of RILEM experts. This generic behaviour of concrete material agrees well with the actual stress-strain curves of concrete at elevated temperatures [17,18,[22][23][24][25]. Also, it has been demonstrated to capture quite satisfactorily experimental results during the heating phase and thus has been generally accepted by authorities and regulators [13,26].…”
Section: The S-e M-t Relation Of Concretesupporting
confidence: 77%
“…This generic behaviour was initially proposed by Schneider [17] and has been approved by a draft committee of RILEM experts. This generic behaviour of concrete material agrees well with the actual stress-strain curves of concrete at elevated temperatures [17,18,[22][23][24][25]. Also, it has been demonstrated to capture quite satisfactorily experimental results during the heating phase and thus has been generally accepted by authorities and regulators [13,26].…”
Section: The S-e M-t Relation Of Concretesupporting
confidence: 77%
“…, T tr is called "thermal induced creep strain" but the definition is different compared to [8]. The pure transient creep will not be calculated numerically within the proposed calculation procedure described above, but the exact extended relationship is given in equation 7.…”
Section: ( )mentioning
confidence: 99%
“…The mechanical analysis is based on these results. There are numerous models available for determining the behavior of ordinary concrete at high temperatures [9,10,11]. In regard to this, there is also high dependency on the type of concrete, used as studies for ultra-high performance concrete have shown (UHPC) [12,13].…”
Section: Introductionmentioning
confidence: 99%